PERAN SEKTOR PERTANIAN DALAM PERTUMBUHAN DAN STABILITAS PRODUK DOMESTIK REGIONAL BRUTO DI KABUPATEN BOJONEGORO - AGUSTONO, AGUSTONO (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2011)
The goals of this research are to understand (1) the play of role of the agricultural sector in growth of GRDP (Gross Regoinal Domestic Product) and the agricultural subsectors in growth of agricultural GRDP; (2) the stability and persistancy of sector and subsector agricultural and the compare with other sectors in economics. The results shows: (1) the play of role the agricultural sector in growth of GDRB, the third in series. It was share about 4.06%-17.34%. In Agricultural subsector, the play of role the food crops subsector in growth of GRDP agricultural sector, the highgest. It was share about 68.02%-71.34%. (2) The agricultural sector more stable compared with other sectors, and the short time lowest persistant compared with other sectors. The animal husbandary subsector more stable compared with other subsectors and food crops most persistant compared with other subsectors.